THE DEVELOPMENT OF ECOTOURISM-BASED FISHERMEN HOUSING ON PANNIKIANG ISLAND - Mimi Arifin; Andi Evi Tri Lestari (Journal of Architecture&ENVIRONMENT, 2017)
Pannikiang Island is an ecotourism area developed by the government of Barru Regency. The existence of ecotourism is expected to bring positive influence to the local community, especially to the local fishermen’s housings. Nevertheless, the housing quality and the welfare of local community are as yet weak. This reserach aims to analyze the proper and integrated development directives with environmental potential. The method used in the research is descriptive method by applying qualitative, quantitative, comparative and spasial analysis. Based on the analysis, the development directives of ecotourism-based housing on Pannikiang Island is semi-intensive tourism activities that give the knowledge as well as the education for tourists, fishermen’s housings is developed as an support accommodation to ecotourism activity and having double function as a homestay and a place where processed marine and mangrove are marketed, enhancing the quality of the ecotourism facilities and infrastructure and furthermore, the development of ecotourism based on community participation.